2005
DOI: 10.1177/107834580401100304
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Telemedicine Practice Into Correctional Medicine: An Evolving Standard

Abstract: The application of telemedicine in corrections has grown rapidly. A comprehensive literature review was conducted to develop a status report on the value that telemedicine has added to health care delivery in the prison setting. When most state and federal correctional telemedicine projects started, operation costs were high and applications were limited. However, with technologies increasingly affordable, access to specialized consultations for prisoners expanded greatly. Further, many legal barriers to servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…[25] This avoids additional costs such as transportation and security measures achieving good satisfaction among the users. [26][27][28] Several studies were performed to help prisons and health services in producing a model for partnership in the delivery of health care in penal establishments. They included models whereby local and Sanitary System augment prison health care through telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…[25] This avoids additional costs such as transportation and security measures achieving good satisfaction among the users. [26][27][28] Several studies were performed to help prisons and health services in producing a model for partnership in the delivery of health care in penal establishments. They included models whereby local and Sanitary System augment prison health care through telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative outcomes data reported varied from correlation between in-person/telemedicine assessment scores, 38 numbers of consultations, 3942 patient satisfaction scores, 43 cost effectiveness, 34,4450 and clinical outcome measures. 5152 Very few studies reported outright failures of telemedicine, 5354 with most finding it offered equivalent or improved care quality 5,42,43,51,52,5570 at an acceptable cost. 8,9,25,31,34,38,43,47,50,53,5659,62,64,69…”
Section: Resultsmentioning
confidence: 99%
“…5152 Very few studies reported outright failures of telemedicine, 5354 with most finding it offered equivalent or improved care quality 5,42,43,51,52,5570 at an acceptable cost. 8,9,25,31,34,38,43,47,50,53,5659,62,64,69…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine applied by surgeons in correctional care can deliver excellent and effective care to inmates without incurring additional costs such as transportation and security measures. 10 Application of communication standards, together with videoconference technologies and health record documentation, provide an effective solution to surgical consultation and facilitate continuity of care. Prior experience with perioperative care guided design of this program.…”
Section: Discussionmentioning
confidence: 99%